Engaged Teaching in Theology and Religion - Harrison, Renee K. author. aut Link
XII, 202 p.
Keywords: This book guides scholars and teachers of theology and religion through a process of self-reflection that leads to intentional, transformative teaching, dialogue, and reform in theological education and religious studies.